Maternal ethnicity and iron status in early childhood in Toronto, Canada: a cross-sectional study. Issue 1 (6th April 2020) - Gunaseelan, Vinusha; Parkin, Patricia C.; Wahi, Gita; Birken, Catherine S.; Maguire, Jonathon L.; Macarthur, Colin; Borkhoff, Cornelia M.
Abstract : Objectives: This study aimed to evaluate the association between maternal ethnicity and iron deficiency (ID) in early childhood, and to evaluate whether infant feeding practices linked to ID differ between maternal ethnic groups. Methods: This was a cross-sectional study of healthy children 1–3 years of age. Adjusted multivariable logistic regression analyses were used to evaluate the association between maternal ethnicity and ID (serum ferritin <12 µg/L) and the association between maternal ethnicity and five infant feeding practices (breastfeeding duration; bottle use beyond 15 months; current formula use; daily cow's milk intake >2 cups; meat consumption). Results: Of 1851 children included, 12.2% had ID. Compared with the European referent group, we found higher odds of ID among children of South Asian and West Asian/North African maternal ethnicities, and lower odds of ID among children of East Asian maternal ethnicity. Statistically significant covariates associated with higher odds of ID included longer breastfeeding duration and daily cow's milk intake >2 cups. Current infant formula use was associated with lower odds of ID. Children of South Asian maternal ethnicity had higher odds of bottle use beyond 15 months of age and lower odds of meat consumption. Conclusions: We found increased odds of ID among children of South Asian and West Asian/Northern African maternal ethnicities. We found a higher odds of feeding practices linked to ID in children of South Asian maternal ethnicity, but not in children of West Asian/North African maternal ethnicity. Culturally tailored approaches to providing guidance to parents on healthy infant feeding practices may be important to prevent ID in early childhood. Trial registration number: NCT01869530 .